The Effect of Special Exercises Based on Neuro-Linguistic Programming (NLP) on Developing Angular Velocity for the Reception Skill in Volleyball (Damu Journal of Sport Sciences, 2025)
Interest has grown among coaches and teachers in studying the psychological aspects of learners in volleyball, with particular emphasis on neuro-linguistic programming (NLP) due to its association with auditory, visual, and kinesthetic processes. NLP serves as a tool that enables learners to change themselves, reform their thinking, enhance their performance and skills, as it relies on experience and testing, leading to tangible results in the learner's skill performance. This study aims to design special exercises based on neuro-linguistic programming for three experimental groups (auditory, visual, and kinesthetic) to develop angular velocity and the reception skill in volleyball among students, and to identify differences between the groups. The researchers employed the experimental method, deemed suitable for the nature of the research problem. Data analysis was conducted using the ready-made Fish Dart program for biomechanical variables specific to the study, alongside an NLP scale and a volleyball reception skill test. The researchers concluded that there was a positive effect on the angular velocity indicator and performance resulting from the use of composite exercises based on neuro-linguistic programming. Notably, the auditory group showed the best development in the angular velocity indicator, which the researchers considered an indicator of learning development through neuro-linguistic programming. The auditory group also demonstrated the best performance development among the three groups using neuro-linguistic programming.